SOSIAL BUDAYA DALAM KONSELING MULTIKULTURAL - Risdawati Siregar (IAIN Padangsidimpuan, 2017)
Bese taw of counseling guidance as factor that have to note by counselor in serving counseling guidance. On multicultural counseling have to see differences of socio culture in process of shapping behavior and attitude of connected individual. Aspect of multicultural counseling have to understood consept of reality and self understanding also social constructional.Multicultural counseling have to hald principle which are principle of privacy counselor and privacy client, so a counselor have to understood characteristic of complexity socio culture in a social life. In serving guidance and counseling its can not be same with solving. So counselor have to understood of value, tradition and habit of a clent.Keywords: Multicultural Counseling